PENGELOLAAN PEMBELAJARAN PKNMENGGUNAKAN MODEL PEMBELAJARAN TPS (THINK PAIR SHARE) DI SMK - Erni Wijaya (Manajer Pendididikan, 2016)
This study aims to know applying learning management of citizenship using learning model TPS (Think Pair Share). This study is the kind of action research (PTK). Subject of thestudy were students of SMKN 2 Bengkulu City. Data collection used test and observation. Percentage of completeness level results and processes the ability to accept the reservation ofstudents in the first cycle pertemuam I reached 24, 4% of students who completed and 75.6% of students did not complete. I cycle II meeting, 41.5% of students who completed and 58.5% of students who did not complete. In the second cycle the first meeting there were 58.5% of studentswho completed and 41.5% of students who did not complete while the second cycle II meeting increased to 100% who pass. Thus the conclusion is that the application of learning management of citizenship by using learning model TPS can improve the learning outcome of SMK Negeri 2 Kota BengkuluKeywords: management, citizenship, Thin Pair Share